Event-Driven Serverless Architectures for High-Scale Customer Support: An Empirical Analysis - Bharath Kumar Reddy Janumpally, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Serverless computing has emerged as a transformative paradigm for building scalable cloud applications, yet its application in customer support systems remains largely unexplored. This article presents a comprehensive analysis of a cloud-native serverless architecture designed to address the scalability challenges inherent in modern customer support operations. The article proposes an event-driven framework that leverages Function-as-a-Service (FaaS) platforms across major cloud providers, demonstrating significant improvements in resource utilization and cost efficiency compared to traditional microservices architectures. Through empirical evaluation and real-world case studies, the article analyzes the performance characteristics of our proposed architecture under varying workload conditions, with particular attention to cold start latencies and event processing throughput. The findings reveal that serverless architectures, when properly implemented with event orchestration systems like Apache Kafka or AWS EventBridge, can provide superior scalability and cost benefits while maintaining system reliability. The article also identifies key architectural patterns and implementation strategies that organizations can adopt to optimize their customer support infrastructure, particularly during peak load periods.
Keywords: Serverless Computing; Customer Support Systems; Event-Driven Architecture; Cloud-Native Scaling; FaaS (Function-as-a-Service)